Country Boundary Agreement as An Effort to Resolve The South China Sea Dispute - Yunita Syofyan (Master of Law Program, Ekasakti University, 2024)
The dispute in the South China Sea Area is a form of large international dispute where the parties are the countries that have interests. The dispute in the South China Sea first occurred when China claimed that the area belonged to the territory unilaterally. The claim made by China refers to the principle of Nine Dash Line, which means that it fully belongs to China's territorial sea so that the North Natuna Sea belonging to Indonesia is also claimed in such a way. The resolution of this dispute has been brought to the forum or International Court, but has not found a common ground or end of the disputed case. Juridical Normative method is a form of research with primary legal materials in the form of legislation (statue approach) and conceptual approach, secondary legal material in the form of a library research. That the settlement of disputes can be carried out peacefully or violently which has been recognized in the custom of international law. However, international dispute resolution efforts do not have a significant impact on the settlement of these disputes. In the 1982 UNCLOS provisions that every coastal state must enforce the law to get justice for the existence of marine waters that own the territory of other countries. Of course, by the existence of negotiations between disputing countries in requesting a detailed explanation of the basics of and the boundaries of the Nine Dash Line.